Pengaruh Ukuran Perusahaan, Debt to Equity Ratio, Kepemilikan Asing, dan Tingkat Implementasi IFRS Terhadap Nilai Perusahaan - Aliefia Rahma Fauzia; Ahalik (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The research aims to test and obtain empirical evidence of size of company, debt to equity ratio, foreign ownership, and implementation ifrs level on firm value. The population in this research are companies in the manufacturing sector listed on Indonsia Stock Exchange (IDX) in the period 2016-2018. The number of research samples obtained is 60 companies with purposive sampling method and the amount of research data obtained is 180. The data analysis method used is multiple linier regression. The simultaneous test show that size of company, debt to equity ratio, foreign ownership, and implementation ifrs level affect stimultaneously on firm value. The partial test result show that size of company has negative affect on firm value, debt to equity ratio has positive affect on firm value, foreign ownership do not affect on firm value, while implementation ifrs level do not affect on firm value.